Knowledge, perception, attitude, and practice of complementary and alternative medicine by health care workers in Garki hospital Abuja, Nigeria - Enole Jennifer Onche; Mojisola Morenike Oluwasanu; Yetunde Olufisayo John-Akinola (BMC, 2024)
Abstract Background Healthcare workers are currently making efforts to offer services that cater to the holistic care needs of their patients. Previous studies have shown that some healthcare workers encounter challenges when advising patients about Complementary and Alternative Medicine (CAM), even though its use is widespread. Many health care workers may not have received formal education or training in CAM and consequently are unable to address their patients' questions about it. This study explored the knowledge, perception, attitude and practice of CAM by healthcare workers in Garki Hospital, Abuja, Nigeria. Methods This was an institution-based cross-sectional study, design and a convergent parallel, mixed methods design was used for data collection. Five (5) healthcare workers were purposively selected as participants for the key informant interviews, while two hundred and fifty (250) selected using a simple random sampling method completed the questionnaire. The data collection instruments used were a key informant interview guide and a 35-item self-administered questionnaire. Knowledge was assessed with a 4-item scale with a maximum score of 8. Perceptions and attitudes were assessed using Likert scales with a maximum score of 45 and 20, respectively. Practice was assessed with a 6-item scale with a maximum score of 18. Qualitative data was analysed using framework analysis. Quantitative data was analysed using descriptive and inferential statistics. Data acquired from both methods were integrated to form the findings. Results The average age of respondents for the quantitative study was 34.0 ± 7.8 years, and they were predominantly females (61.2%) with one to ten years of work experience (68.8%). The mean knowledge, perception and attitude scores were 1.94 ± 1.39, 13.08 ± 2.34 and 32.68 ± 6.28, respectively. Multiple linear regression result showed that knowledge (t = 2.025, p = 0.044) and attitude (t = 5.961, p = 0.000) had statistically significant effects on the practice of CAM. Qualitative data revealed that the majority of the participants perceive CAM favourably, provided it is properly introduced into mainstream medicine with evidence of safety and research to prove its efficacy. Conclusion The study has shown the gaps in knowledge and the practices of CAM by conventional medical practitioners. This has implications for their ability to counsel and refer patients who may require CAM therapies. Policy, research and programmatic initiatives that seek to enhance their knowledge of CAM, and improve collaboration with CAM practitioners are recommended.